Pengaruh Pemasaran Digital, Kualitas Produk dan Penerapan E-Wallet terhadap Kinerja UMKM pada Car Free Night dan Car Free Day di Kabupaten Sumbawa - Ladya Della Rose; Tomy Dwi Cahyono (SENTRI: Jurnal Riset Ilmiah, 2026)
The rapid transformation of the modern economy necessitates Micro, Small, and Medium Enterprises (MSMEs) to integrate digital ecosystems and consistently enhance product value. This study aims to analyze the impact of digital marketing, product quality, and e-wallet adoption on the performance of MSMEs operating at the Car Free Day (CFD) and Car Free Night (CFN) in Sumbawa Regency. Characterized by massive crowds and limited operational hours, this unique open-market dynamic demands highly agile business strategies. Employing a quantitative survey design, primary data were collected from 100 purposively selected MSME actors and analyzed using multiple linear regression. The empirical findings reveal that the independent variables collectively explain 71.5% of the variance in business performance. Partially, digital marketing exhibits a positive and significant effect on MSME performance (t = 3.304, p = 0.001), functioning as a vital pre-event promotional bridge. Product quality emerges as the strongest and most dominant determinant (t = 3.640, p < 0.001), serving as the primary competitive advantage for customer retention. Additionally, e-wallet implementation significantly boosts operational efficiency (t = 3.000, p = 0.003) by accelerating cashless transactions during peak times. Conclusively, the synergistic integration of proactive digital marketing, stringent product quality maintenance, and cashless payment adoption is fundamentally imperative for MSMEs to maximize revenue and secure long-term market sustainability.